A method for optimizing the conductivity of a laser sputtered metal surface layer on a plastic substrate LMC

CN122991758APending Publication Date: 2026-10-27GUANGDONG XUNCHUANG COMMUNICATIONS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611112727.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-25
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

该技术需依赖化学镀工序完成金属化,金属层厚度和均匀性受镀液参数影响较大

Benefits of technology

[0043]一、本发明通过在塑料基材表面预先制备嵌段共聚物自组装薄膜,利用薄膜中功能链段的化学官能团与金属原子之间的配位键合作用,在基材表面构建出周期性分布的纳米级化学锚点,在LMC激光溅射过程中,熔融金属液滴到达表面时,金属原子优先在这些化学锚点处被捕获并稳定形核,继而从锚点位置沿径向向外铺展生长,相邻锚点处生长的金属区域在纳米尺度上相互搭接融合,形成连续、完整的导电网络,从而克服了塑料基材因表面自由能低和化学惰性强造成的熔融金属液滴随机孤立生长、无法构成连续导电通路的问题,在完整保留LMC一步沉积工艺优势、不引入任何化学镀工序的前提下,使溅射金属层的导电性获得了实质性改善。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122991758A_ABST
    Figure CN122991758A_ABST
Patent Text Reader

Abstract

The application discloses a kind of plastic substrate LMC laser sputtering metal surface layer's conductivity optimization method, it is related to laser micro-melting technology field, the method is first prepared a layer of block copolymer self-assembly film on plastic substrate surface, the film contains anchor segment and functional segment, forms nanoscale periodic microphase separation structure after annealing, and functional segment provides chemical anchor point on surface;Again, donor metal film is transferred to substrate surface by LMC laser sputtering, and molten metal atom is captured by chemical anchor point coordination and preferentially nucleates, and continuous conductive network is formed by radial spreading and mutual lap joint.The application avoids chemical plating and high-temperature process, does not change the intrinsic properties of plastic substrate, process is simple, can be applied to various plastic substrates and metal system, and the resistivity of obtained conductive layer is significantly reduced, has good application prospect in the direction such as flexible circuit, electronic interconnection and noble metal manufacturing electric contact.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of laser micro-cladding technology, specifically a method for optimizing the conductivity of LMC laser sputtered metal surfaces on plastic substrates. Background Technology

[0002] Laser micro-cladding (LMC) technology transfers a thin metal film from a donor substrate to a recipient substrate surface via laser sputtering, directly forming a conductive metal layer. It shows promise in the manufacture of electronic interconnects, flexible circuits, and electrical contact materials. Applying LMC technology to the metallization of plastic substrates allows for the deposition of a conductive metal layer in a single step without the introduction of chemical plating or electroplating processes.

[0003] Currently, surface metallization of plastic substrates widely employs Laser Direct Structuring (LDS) technology or chemical plating processes. Patent publication number CN103313521B discloses a method for manufacturing a conductive structure on the surface of a plastic part. This method involves adding mineral powder to the plastic material, enhancing the surface adsorption capacity of the irradiated area through laser irradiation, and then forming a thin metal layer through chemical activation and reduction. This technology relies on a chemical plating process for metallization, and the thickness and uniformity of the metal layer are significantly affected by the plating solution parameters. Laser-Induced Forward Transfer (LIFT) technology has been used to prepare conductive coatings on polymer substrates, but research focuses on the influence of process parameters such as laser energy density and scanning speed on the performance of conductive coatings, without addressing surface pretreatment and interface nucleation control of the plastic substrate. Patent publication number CN117637246B discloses a laser-induced forward transfer method for forming a highly conductive metal structure. This method reduces the resistivity of the metal structure by adding a thermal annealing step at over 800°C after transfer, but this high-temperature treatment is not suitable for plastic substrates.

[0004] When LMC technology is directly applied to plastic substrates, the low surface free energy and strong chemical inertness of plastic substrates make it difficult for molten metal droplets to spread uniformly on the plastic surface. This results in isolated island-like nucleation and growth, leading to a lack of a continuous conductive network in the sputtered metal layer and extremely poor conductivity. In existing technologies, the nucleation process after LMC transfer of metal droplets is uncontrollable, and there is a lack of technical means to actively induce uniform nucleation of metal droplets on the plastic substrate surface at the molecular or nanoscale. How to achieve controlled nucleation and continuous spread of metal droplets on the plastic substrate surface while maintaining the advantages of one-step LMC deposition is a pressing technical problem that needs to be solved. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a method for optimizing the conductivity of LMC laser sputtered metal layers on plastic substrates. By forming a block copolymer self-assembled film on the surface of the plastic substrate, the coordination bonding between the chemical functional groups of the functional segments in the film and the metal atoms induces the metal droplets to preferentially nucleate at periodically distributed chemical anchor points. This allows the metal layer to spread radially in a controlled manner from the nanoscale and overlap with each other to form a continuous conductive metal layer. Thus, the conductivity of the LMC sputtered metal layer is significantly optimized without introducing a chemical plating process or changing the intrinsic composition of the plastic substrate.

[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a method for optimizing the conductivity of a metal surface layer on a plastic substrate by LMC laser sputtering, the method comprising the following steps:

[0007] Step 1: A block copolymer self-assembled film is formed on the surface of a plastic substrate. The block copolymer includes anchoring segments and functional segments. The anchoring segments are attached to the surface of the plastic substrate through intermolecular interactions. The functional segments carry chemical functional groups that can coordinate with metal atoms. After annealing, the block copolymer self-assembled film forms a nanoscale periodic microphase separation structure. The functional segments form periodically distributed chemical anchors on the surface of the self-assembled film.

[0008] Step 2: Using LMC laser sputtering, a metal film is transferred from the donor substrate to the surface of the plastic substrate. The molten metal droplets generated by sputtering impact the surface of the self-assembled film. The metal atoms in the metal droplets coordinate and bond with the chemical anchor points, preferentially nucleating at the chemical anchor points and spreading radially to form a continuous conductive metal layer.

[0009] A block copolymer self-assembled film is formed on the surface of a plastic substrate. The film is stably attached by the intermolecular interaction between the anchoring segments and the substrate. The chemical functional groups of the functional segments coordinate with the metal atoms, so that the molten metal droplets preferentially nucleate at the chemical anchor points. This avoids the random island growth of metal droplets on low surface energy plastic surfaces and enables the sputtered metal layer to form a continuous conductive path from the nanoscale.

[0010] Further, in step one, the block copolymer is a polystyrene-intercalated-poly(4-vinylpyridine), the anchoring segment is a polystyrene segment, the functional segment is a poly(4-vinylpyridine) segment, the chemical functional group is a pyridine nitrogen atom, the number average molecular weight of the block copolymer is 30,000 g / mol to 150,000 g / mol, and the mass fraction of the poly(4-vinylpyridine) segment is 25% to 50%.

[0011] Polystyrene-intercalated-poly(4-vinylpyridine) was used as a block copolymer. The polystyrene segments have good compatibility with a variety of engineering plastics. The coordination energy between the pyridine nitrogen atoms of the poly(4-vinylpyridine) segments and transition metal atoms such as copper and silver can reach tens to hundreds of kJ / mol. Capture and nucleation induction can be completed in the nanosecond-level impact process. The strength of this coordination is sufficient to overcome the inertia of the plastic surface.

[0012] Furthermore, in step one, the block copolymer is selected from any one of the following groups:

[0013] Polystyrene-intercalated poly(2-vinylpyridine);

[0014] Polymethyl methacrylate-intercalated (4-vinylpyridine);

[0015] Styrene-vinylpyridine-styrene triblock copolymer;

[0016] Block copolymers with thiol functional groups grafted onto their surfaces;

[0017] Surface grafted block copolymers containing amino functional groups.

[0018] In polystyrene-intercalated poly(2-vinylpyridine), the steric hindrance of the pyridine nitrogen atom at the 2-position is less than that at the 4-position, resulting in a faster coordination reaction rate, making it suitable for LMC processes that require shorter nucleation time windows. In polymethyl methacrylate-intercalated poly(4-vinylpyridine), the PMMA segment has a stronger affinity for ester-containing plastic substrates, which can improve the adhesion stability of self-assembled films.

[0019] Furthermore, in step one, the method for preparing the block copolymer self-assembled film includes spin coating or dip coating. The spin coating method has a spin coating speed of 2000 rpm to 4000 rpm and a spin coating time of 30 seconds to 60 seconds. The dip coating method has a lifting speed of 0.5 mm / s to 2 mm / s and a dip coating time of 30 seconds to 60 seconds. The thickness of the block copolymer self-assembled film is 10 nm to 50 nm.

[0020] In spin coating, rotating at 2000 to 4000 rpm for 30 to 60 seconds can produce block copolymer films with uniform thickness and no pinholes; in dip coating, the film thickness is controlled by a pulling speed of 0.5 to 2 mm / s. Both methods can be completed at room temperature without damaging the plastic substrate and have good process compatibility.

[0021] Furthermore, in step one, the annealing process is carried out in a vacuum oven at a temperature of 120°C to 150°C for 2 to 4 hours, and the size of the nanoscale periodic microphase separation structure is 5 nm to 20 nm.

[0022] Vacuum annealing at 120–150 °C for 2–4 hours allows the block copolymer molecular chains to rearrange through thermal motion, reaching thermodynamic equilibrium and forming a periodic microphase-separated structure of 5–20 nm. This nanoscale matches the metal grain size, enabling the areal density of chemical anchor points to reach 10. 15 Up to 10 16 m -2 The metal regions deposited at adjacent anchor points can overlap to form a continuous network.

[0023] Furthermore, in step one, before forming the block copolymer self-assembled film, the plastic substrate is subjected to surface pretreatment, which is oxygen plasma treatment or ultraviolet ozone treatment. The oxygen plasma treatment has a power of 50W to 100W and a treatment time of 30 seconds to 60 seconds.

[0024] Pretreatment with oxygen plasma or ultraviolet ozone before coating block copolymers can introduce polar groups such as hydroxyl and carbonyl groups onto the plastic surface, increasing the surface energy from 30 to 40 mN / m to 50 to 70 mN / m. This significantly improves the wetting and spreading ability of the block copolymer solution, while also enhancing the interaction between the anchoring segments and the substrate, preventing the self-assembled film from falling off during LMC sputtering.

[0025] Furthermore, in step two, the LMC laser sputtering process uses a laser wavelength of 532nm or 1064nm, a laser pulse width of 10ns to 50ns, and a laser energy density of 1×10⁻⁶. 5 W / cm² up to 5×10 5 W / cm², the distance between the donor substrate and the plastic substrate is 50μm to 200μm.

[0026] Using 532nm or 1064nm nanosecond pulsed lasers, the energy density is controlled at 1×10 5 Up to 5×10 5 With a capacity of W / cm², the metal film can be completely melted and vaporized within 10 to 50 ns, forming molten droplets with a diameter of 5 to 30 μm that impact the acceptor surface at a speed of 1 to 10 m / s. This energy window ensures sufficient metal transfer without causing thermal damage to the block copolymer layer and the plastic substrate.

[0027] Furthermore, in step two, the thickness of the metal film is 200 nm to 500 nm, and the metal film is selected from pure copper film, pure silver film, copper-silver alloy film, copper-nickel alloy film, gold film, or platinum film.

[0028] When the metal film thickness is 200 to 500 nm, the amount of metal transferred in a single LMC sputtering is just enough to overlap the radial growth region around the chemical anchor with the adjacent anchor. Pure copper and pure silver have the highest electrical conductivity, while copper-silver alloys and copper-nickel alloys can balance conductivity and resistance to electrochemical corrosion. Gold and platinum are suitable for high-reliability electrical contacts and corrosion-resistant applications.

[0029] Furthermore, step two also includes performing at least one repeated LMC laser sputtering on the continuous conductive metal layer deposited on the surface of the plastic substrate, so that the continuous conductive metal layer accumulates and thickens, and the final thickness of the continuous conductive metal layer is 500 nm to 5 μm.

[0030] After the initial LMC sputtering forms a continuous underlayer, at least one repeated sputtering is performed in the same area. Subsequent metal droplets are deposited directly on the existing metal layer, achieving uniform thickness increase without relying on the induction of the block copolymer layer. By controlling the number of sputtering operations, the metal layer thickness can be accumulated from an initial 200 to 500 nm to 5 μm, and the resistivity can be reduced from approximately 10 μΩ·cm in a monolayer to 3 to 5 μΩ·cm.

[0031] Furthermore, the plastic substrate is selected from any one of the following groups:

[0032] Polycarbonate;

[0033] Acrylonitrile-butadiene-styrene copolymer;

[0034] Polymethyl methacrylate;

[0035] Polypropylene;

[0036] Polyethylene;

[0037] Polyethylene terephthalate;

[0038] Polyetheretherketone;

[0039] Liquid crystal polymer;

[0040] Polystyrene.

[0041] Amorphous plastics such as polycarbonate, ABS, and polymethyl methacrylate have good compatibility with PS segments and can be directly spin-coated to form self-assembled films. Semi-crystalline or high-performance plastics such as polypropylene, polyethylene, and polyetheretherketone can also obtain stable block copolymer coatings after oxygen plasma pretreatment. This method does not alter the intrinsic composition of the plastic, is applicable to various substrate types, and possesses good process versatility.

[0042] Compared with existing technologies, this method for optimizing the conductivity of LMC laser sputtered metal surfaces on plastic substrates has the following advantages:

[0043] I. This invention pre-prepares a block copolymer self-assembled film on the surface of a plastic substrate. Utilizing the coordination bonding between the chemical functional groups of the functional segments in the film and metal atoms, periodically distributed nanoscale chemical anchors are constructed on the substrate surface. During LMC laser sputtering, when molten metal droplets reach the surface, metal atoms are preferentially captured and stably nucleated at these chemical anchors, subsequently spreading radially outward from the anchor locations. The metal regions grown at adjacent anchors overlap and fuse at the nanoscale, forming a continuous and complete conductive network. This overcomes the problem of random, isolated growth of molten metal droplets due to the low surface free energy and strong chemical inertness of plastic substrates, which prevents the formation of continuous conductive pathways. While fully retaining the advantages of the one-step LMC deposition process and without introducing any chemical plating steps, the conductivity of the sputtered metal layer is substantially improved.

[0044] Second, the block copolymer self-assembled film preparation process used in the method of this invention is simple. The anchored segments form a reliable adhesion to the plastic substrate through intermolecular forces. It shows good adaptability to various engineering plastics such as polycarbonate, polyester, and polyetheretherketone. The entire process is completed under low temperature conditions that the plastic substrate can withstand, without changing the intrinsic molecular structure and bulk mechanical properties of the substrate. By rationally selecting different types of block copolymers and various metal systems such as pure copper, pure silver, and gold, it can flexibly adapt to different application scenarios, raising the applicability and process compatibility of LMC technology in the fields of flexible circuits, electronic interconnects, and electrical contact precious metal material manufacturing to a new level.

[0045] Other advantages, objectives and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination or study, or may be learned from the practice of the invention. Attached Figure Description

[0046] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0047] Figure 1 This is a flowchart illustrating the overall process flow of the method of the present invention.

[0048] Figure 2 This is a timeline diagram illustrating the process of metal droplet transfer, impact on the acceptor surface, capture by chemical anchors, preferential nucleation, and radial spread to form a continuous conductive network during LMC laser sputtering in this invention. Detailed Implementation

[0049] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with the accompanying drawings and preferred embodiments, is provided below.

[0050] In the first specific embodiment, such as Figure 1 As shown, the overall process flow of this embodiment is as follows: First, oxygen plasma pretreatment is performed on the surface of the plastic substrate. Then, a block copolymer self-assembled film is formed by spin coating. After vacuum annealing, nanoscale periodic chemical anchors are obtained. Subsequently, LMC laser sputtering is used to transfer a metal film to the substrate surface. Molten metal droplets preferentially nucleate at the chemical anchors and spread radially to form a continuous conductive metal layer. If thickness is required, LMC sputtering can be repeated until the target thickness is achieved. The specific implementation steps of the present invention will be described in detail below with reference to the polycarbonate substrate and the pure copper metal system.

[0051] Polycarbonate sheets were selected as the plastic substrate, with dimensions of 50mm × 50mm × 2mm. Polycarbonate is an engineering plastic with excellent light transmittance and impact resistance, and is widely used in electronic device housings and flexible circuit boards. However, polycarbonate has a low surface free energy, approximately 32mN / m to 35mN / m when untreated, making it difficult for molten metal droplets to spread on its surface.

[0052] First, the polycarbonate substrate undergoes surface pretreatment. The substrate is placed in the chamber of an oxygen plasma treatment device, with the chamber evacuated to below 5 Pa. Oxygen with a purity of 99.99% is introduced at a flow rate of 20 sccm, and the RF power is set to 80 W for 45 seconds. During the oxygen plasma treatment, high-energy oxygen ions and reactive oxygen radicals bombard the polycarbonate surface, causing partial breakage of the carbonate bonds and benzene rings in the surface molecular chains and introducing oxygen-containing polar groups. After treatment, the substrate is removed, and the contact angle of surface water droplets is measured using a contact angle meter. The contact angle decreased from approximately 82° before treatment to approximately 28°, resulting in an increase in surface energy to approximately 58 mN / m. This surface energy level is sufficient to ensure the uniform spreading of the subsequent block copolymer solution.

[0053] Next, a self-assembled block copolymer film was prepared. A polystyrene-intercalated-poly(4-vinylpyridine) diblock copolymer was selected as the film-forming material. This copolymer has a number-average molecular weight of 80,000 g / mol and a molecular weight distribution index of 1.08, with a poly(4-vinylpyridine) segment mass fraction of 35%. The polystyrene segment acts as the anchoring segment, and its benzene ring interacts strongly with the polycarbonate substrate surface through van der Waals forces and dispersion forces. The poly(4-vinylpyridine) segment acts as the functional segment; the nitrogen atom on its pyridine ring carries a lone pair of electrons, which can form coordinate bonds with the empty d orbitals of transition metal atoms such as copper and silver, with coordinate bond energies ranging from approximately 70 kJ / mol to 90 kJ / mol.

[0054] The block copolymer was dissolved in toluene (analytical grade) to prepare a 1.2% (w / w) solution. The solution was stirred at room temperature for 4 hours to ensure complete dissolution and a homogeneous, transparent solution. The solution was filtered using a 0.22 μm PTFE filter to remove any potentially aggregated particles. A polycarbonate substrate pretreated with oxygen plasma was placed horizontally on the suction cup of a spin coater, and vacuum adsorption was applied to fix the substrate. Approximately 0.5 mL of the block copolymer solution was pipetted and added dropwise to the center of the substrate. The spin coating process was initiated: the first stage involved rotating at 500 rpm for 5 seconds to pre-spread the solution on the substrate surface; the second stage involved rotating at 3000 rpm for 45 seconds, using centrifugal force to evenly distribute the solution and remove excess solution. During spin coating, the toluene solvent rapidly evaporated, and the block copolymer molecules formed a uniformly thick solid film on the substrate surface.

[0055] After spin coating, the substrate coated with the block copolymer film was transferred to a vacuum oven for annealing. The vacuum level in the oven was maintained below 10 Pa, the annealing temperature was set to 135℃, and the annealing time lasted for 3 hours. The annealing process is a key step in the formation of a periodic microphase separation structure in the self-assembled film. At the annealing temperature, the block copolymer molecular chains acquire sufficient thermal energy, and microscale phase separation occurs between the polystyrene segments and the poly(4-vinylpyridine) segments due to chemical incompatibility. Constrained by the volume ratio of the two segments in the block copolymer molecule, the phase separation does not extend indefinitely, but forms a nanoscale periodic ordered structure after reaching thermodynamic equilibrium. Specifically, the poly(4-vinylpyridine) segments aggregate to form spherical or short columnar domains with a diameter of approximately 12 nm, which are uniformly dispersed in the continuous polystyrene matrix. On the film surface after annealing, the enriched regions formed by the poly(4-vinylpyridine) domains on the surface are chemical anchors, and these anchors exhibit an approximately hexagonal distribution pattern on the surface. The center-to-center spacing between the anchors is approximately 22 nm, from which the areal density of the chemical anchors is calculated to be approximately 2.1 × 10⁻⁶. 15 m-2 .

[0056] After annealing, the substrate was slowly cooled to room temperature in the furnace at a rate of approximately 1°C / min to avoid stress in the film caused by rapid cooling. After removing the sample, the surface morphology of the film was characterized using atomic force microscopy (AFM). Imaging with a 1μm × 1μm scanning range in tapping mode clearly revealed a periodic alternating pattern of light and dark areas. The dark areas corresponded to poly(4-vinylpyridine) domains, i.e., the chemical anchor points, while the bright areas corresponded to the polystyrene matrix. The overall film thickness was measured using an ellipsometer, finding to be 28 nm, which falls within the target range of 10 nm to 50 nm. This thickness ensures sufficient depth for the chemical anchor points to effectively capture and guide molten metal droplets without becoming a thermal barrier layer during LMC sputtering due to excessive film thickness.

[0057] After the block copolymer self-assembled film is prepared, the LMC laser sputtering process in step two can be performed. The LMC laser sputtering system includes a nanosecond pulsed laser, a donor substrate fixing platform, a acceptor substrate fixing platform, and a precision displacement control system. The laser output wavelength is 1064 nm. This wavelength of laser light has good absorption efficiency for metal films and high transmittance for polycarbonate substrates, which helps to reduce heat accumulation on the substrate. The laser pulse width is set to 25 ns, and the single pulse energy is adjusted by an attenuator to ensure that the laser energy density reaching the surface of the donor substrate is 2.5 × 10⁻⁶. 5 W / cm².

[0058] The donor substrate is an optical glass sheet measuring 60mm × 60mm × 1mm, with a pure copper thin film pre-deposited on its surface using an electron beam evaporation process. The pure copper thin film has a thickness of 350nm and a uniformity within ±5%. The donor and acceptor substrates are placed face-to-face and parallel, with the distance between them precisely controlled at 120μm using a fine-tuning mechanism. This distance was chosen to account for the expansion characteristics of the plasma plume and the trajectory of the molten droplets during laser sputtering. A distance that is too small can easily cause contamination and short circuits between the donor and acceptor, while a distance that is too large will result in an excessively wide droplet dispersion range, affecting the accuracy of the deposition pattern.

[0059] The acceptor substrate is a polycarbonate sheet coated with a block copolymer self-assembled film, which is fixed on a three-dimensional moving platform. By controlling the platform's movement trajectory via computer, metal layers with arbitrary two-dimensional patterns can be deposited on the substrate. In this embodiment, a linear array is used as an example for conductivity testing. The designed linewidth is 80 μm, the line length is 10 mm, and a total of 5 parallel lines are deposited.

[0060] The laser operates in single-pulse mode with a repetition frequency of 10 Hz. The laser beam, focused by a focusing lens, irradiates the interface between the copper thin film and the glass through a transparent donor substrate. Within the extremely short laser pulse duration, the copper thin film at the interface absorbs laser energy, and its temperature rapidly rises above the melting and boiling points of copper, causing partial melting and vaporization. The recoil pressure generated by the vaporized copper tears the molten copper film above into numerous micron-sized droplets. These droplets, propelled by the vaporization products, fly towards the acceptor substrate with an initial velocity of approximately 5 m / s.

[0061] like Figure 2 As shown, when molten copper droplets impact the self-assembled block copolymer film on the surface of the acceptor substrate, the droplets first contact the chemical anchoring regions on the film surface. The poly(4-vinylpyridine) segments at these chemical anchoring points are rich in pyridine nitrogen atoms, and the lone pair electrons on the nitrogen atoms coordinate with the empty 3d orbitals of the copper atoms. The binding energy of this coordination is significantly higher than the non-specific van der Waals interaction energy between copper atoms and polystyrene segments or the plastic substrate surface. Therefore, copper atoms reaching the surface are preferentially captured by the chemical anchoring points, forming stable atomic clusters at the anchoring sites, which become nucleation centers for subsequent copper atom deposition.

[0062] As more copper droplets arrive, copper atoms accumulate layer by layer outwards along the circumference of each chemical anchor point, using these anchor points as nucleation centers. Since the distance between the chemical anchor points is only about 22 nm, the copper nanocrystals grown at adjacent anchor points begin to contact and fuse when their diameter expands to about 20 nm, forming a continuous conductive network structure. This process occurs on a timescale of nanoseconds to microseconds, synchronized with the droplet flight and deposition process generated by a single laser pulse. Copper atoms in the copper droplets that were not deposited at the chemical anchor points also deposit on the already formed copper layer, further increasing the thickness and density of the metal layer.

[0063] After a single LMC laser sputtering operation, the resistance of the deposited copper conductive lines was measured using a four-probe resistivity meter. The four probes were evenly spaced along the length of the lines, with a probe spacing of 2 mm. The test results showed that the resistivity of the copper conductive layer formed by a single sputtering operation was approximately 10.5 μΩ·cm, about 6.3 times that of bulk pure copper (1.68 μΩ·cm). This resistivity level represents a significant improvement over the insulating state of discontinuous island deposition without the introduction of self-assembled thin films, but it still falls short of the requirements for high conductivity applications. The high resistivity is mainly due to the relatively thin copper layer formed by a single sputtering operation, approximately 200 nm to 250 nm, and the presence of a small number of pores and grain boundaries within the metal layer.

[0064] To achieve superior conductivity, the region where a continuous conductive layer had formed was subjected to repeated LMC laser sputtering. A total of three sputtering cycles were performed, with each cycle using identical process parameters to the first. As the number of sputtering cycles increased, the copper layer thickness gradually accumulated, reaching approximately 950 nm after four sputtering cycles. The resistivity of the copper wire was measured again using the four-probe method, and the result showed a decrease to approximately 4.2 μΩ·cm, about 2.5 times the resistivity of bulk copper.

[0065] The microstructure of the final copper conductive layer was observed using scanning electron microscopy. Secondary electron images revealed a uniform and dense microstructure on the copper layer surface, without obvious cracks, pores, or island-like discontinuities. The copper grains were uniform in size, with an average grain diameter of approximately 45 nm and clear grain boundaries. This uniform nucleation and growth mode induced by chemical anchoring allows the copper grains to interconnect at the nanoscale, fundamentally avoiding the discontinuity problem in the metal layer caused by low surface energy substrates.

[0066] The beneficial effects of this embodiment will now be explained. In a comparative test without the use of block copolymer self-assembled films, under the same LMC sputtering conditions, the copper deposition on the polycarbonate surface appeared as isolated micron-sized island-like particles, which were not interconnected and had an overall resistivity >10. 6 μΩ·cm, which is in an electrically insulating state. By introducing the self-assembled thin film technology of this invention, a continuous conductive network is formed in a single sputtering operation, reducing the resistivity to the order of 10 μΩ·cm. Repeated sputtering further reduces it to 4.2 μΩ·cm, achieving an improvement in conductivity of more than six orders of magnitude. This embodiment fully demonstrates the entire implementation process of the technical solution of this invention on a polycarbonate substrate and the technical effects achieved.

[0067] In the second specific embodiment, polyethylene terephthalate (PET) film is selected as the plastic substrate. PET film is widely used in flexible electronics and printed circuits. Its thinness and flexibility place different demands on the adhesion and conductivity of the metal conductive layer. In this embodiment, the PET film used is 125 μm thick and cut into 60 mm × 60 mm sheets.

[0068] The PET film underwent surface pretreatment using an ultraviolet ozone cleaning system. The PET film was placed flat within the ultraviolet ozone treatment chamber, where a dual-wavelength ultraviolet lamp emitted light at wavelengths of 185nm and 254nm for 60 seconds. The ultraviolet light irradiation caused a photo-oxidation reaction in the polyester molecular chains on the PET surface, generating oxygen-containing functional groups such as carboxyl and hydroxyl groups. The surface energy increased from approximately 38 mN / m before treatment to approximately 62 mN / m.

[0069] The block copolymer selected was a styrene-vinylpyridine-styrene triblock copolymer with a number-average molecular weight of 60,000 g / mol and a poly(4-vinylpyridine) segment mass fraction of 40%. Compared to diblock copolymers, the triblock structure allows the polystyrene segments at both ends to interact with the substrate surface and the air interface, respectively, which is beneficial for forming a more ordered and stable periodic structure during annealing. The block copolymer was dissolved in a mixed solvent of toluene and tetrahydrofuran at a volume ratio of 4:1 to prepare a 1.0% (w / w) solution.

[0070] Self-assembled films were prepared on the surface of PET film using a dip-coating method. The pretreated PET film was vertically clamped in the fixture of a dip-coating apparatus and slowly pulled out of the block copolymer solution at a stable pulling speed of 1.0 mm / s. During the pulling process, a uniform liquid film formed on the PET surface, and the block copolymer film remained after the solvent evaporated. After dip-coating, the sample was transferred to a vacuum oven and annealed at 130°C for 3.5 hours. After annealing, a periodic microphase separation structure was formed, with poly(4-vinylpyridine) domains forming chemical anchors on the surface. The domain size was approximately 15 nm, the spacing was approximately 25 nm, and the film thickness was approximately 20 nm.

[0071] The LMC laser sputtering process parameters are as follows: laser wavelength 532nm, pulse width 18ns, energy density 1.8×10⁻⁶. 5 The donor substrate is a quartz glass plate with a 400 nm pure silver film deposited on it, and the distance between the donor and acceptor is 80 μm. Pure silver was chosen as the metal layer material because it has the highest electrical conductivity of all metals, with a bulk silver resistivity of 1.59 μΩ·cm, and also has excellent oxidation resistance.

[0072] After a single sputtering, the silver conductive layer forms a continuous conductive network under the chemical anchoring induction of the block copolymer film, with a resistivity of approximately 9.8 μΩ·cm. Two subsequent sputtering cycles were performed, accumulating a silver layer thickness of approximately 680 nm, with a final resistivity of 3.8 μΩ·cm, approximately 2.4 times the resistivity of bulk silver.

[0073] This embodiment further demonstrates the applicability of the present invention's technical solution to flexible PET substrates. The block copolymer self-assembled film maintains structural stability during the bending process of the flexible substrate, and the coordination bonding between the chemical anchors and the metal layer maintains good adhesion even when the substrate is subjected to bending strain.

[0074] In the third specific embodiment, the plastic substrate is selected as polyetheretherketone (PEEK) sheet, which is a high-performance thermoplastic engineering plastic with a long-term service temperature of up to 250°C. It has excellent chemical corrosion resistance and mechanical strength and is used as a support material for insulating structural components and electrical contact components in aerospace and high-end electronic devices.

[0075] PEEK surfaces are chemically inert, making reliable metallization difficult to achieve using conventional methods. In this embodiment, the PEEK surface is first treated with oxygen plasma at a radio frequency power of 100W for 60 seconds. Because the PEEK molecular chain contains carbonyl and ether bonds, plasma treatment introduces more oxygen-containing polar groups onto the surface, increasing the surface energy from approximately 30 mN / m before treatment to approximately 52 mN / m.

[0076] The block copolymer used was polymethyl methacrylate (PMMA)-poly(4-vinylpyridine) with a number-average molecular weight of 100,000 g / mol and a poly(4-vinylpyridine) segment mass fraction of 30%. Strong dipole-dipole interactions and potential hydrogen bonding exist between the ester groups in the PMMA segments and the carbonyl groups and ether bonds in the PEEK molecular chains, resulting in superior adhesion stability of the self-assembled film on the PEEK surface compared to polystyrene-based block copolymers. The block copolymer was dissolved in butyl acetate at a mass concentration of 0.8%, spin-coated at 2500 rpm for 40 seconds, and then vacuum annealed at 145 °C for 2.5 hours. After annealing, a microphase-separated structure with a period of approximately 18 nm was formed, and the film thickness was 35 nm.

[0077] LMC laser sputtering process parameters: laser wavelength 1064nm, pulse width 30ns, energy density 3.0×10⁻⁶ 5 The donor substrate is a glass slide with a 300 nm copper-nickel alloy film deposited on it, with a copper-nickel mass ratio of 90:10 and a donor-acceptor distance of 150 μm. While maintaining high electrical conductivity, the addition of nickel improves the metal layer's resistance to electrochemical corrosion and electromigration.

[0078] After a single sputtering process to form a continuous copper-nickel alloy conductive layer, three repeated sputtering cycles were performed, resulting in a cumulative metal layer thickness of approximately 1.1 μm and a final resistivity of 5.5 μΩ·cm. This resistivity level is slightly higher than that of pure metal, which is due to the increase in solid solution resistivity caused by the addition of nickel, and is considered normal. After a 100-hour thermal aging test at 200°C, the resistivity change of the copper-nickel alloy conductive layer did not exceed 8%, demonstrating good thermal stability. In contrast, the resistivity of the pure copper conductive layer increased by approximately 22% under the same thermal aging conditions, indicating that the copper-nickel alloy has better adaptability to high-temperature applications.

[0079] This embodiment verifies the implementation effect of the present invention on high-performance engineering plastic substrates, and demonstrates the adaptability of flexible selection of block copolymer types to different substrate types, as well as the application expansion of different metal material systems.

[0080] In the fourth specific embodiment, gold is used as the conductive layer metal to meet the requirements of manufacturing precious metal materials for electrical contacts. Gold has a bulk resistivity of 2.44 μΩ·cm, which is slightly higher than that of copper and silver, but its chemical inertness gives it an irreplaceable advantage in electrical contact applications, especially in scenarios requiring low contact resistance and high reliability.

[0081] The plastic substrate is made of liquid crystal polymer sheet, which exhibits excellent dimensional stability and low moisture absorption. After 40 seconds of UV ozone treatment, the surface energy increases from approximately 34 mN / m to approximately 55 mN / m. The block copolymer is polystyrene-intercalated poly(2-vinylpyridine), with a number-average molecular weight of 45,000 g / mol and a poly(2-vinylpyridine) segment mass fraction of 28%. Compared to poly(4-vinylpyridine), the benzene ring around the pyridine nitrogen atom at position 2 has less steric hindrance, resulting in more favorable coordination reaction kinetics for metal atoms. This allows for faster capture of gold atoms within the extremely short droplet contact and cooling time window during laser sputtering.

[0082] LMC laser sputtering uses glass with a 500nm gold film deposited as the donor substrate, with a laser wavelength of 532nm, a pulse width of 15ns, and an energy density of 4.0×10⁻⁶. 5 W / cm², spacing 100μm. Gold has a high melting point of approximately 1064℃, requiring a higher laser energy density than copper and silver. After forming a gold conductive network through a single sputtering, four repeated sputtering processes are performed, resulting in a cumulative gold layer thickness of approximately 1.5μm and a resistivity of approximately 5.0μΩ·cm, about twice the resistivity of bulk gold.

[0083] Electrical contact performance tests were performed on the gold conductive layer. The contact resistance was measured using the standard four-wire method. Under a contact pressure of 0.5 N, the contact resistance between a 1 mm diameter gold ball contact and the gold conductive layer was 3.2 mΩ. After 5000 mechanical insertion and removal cycles, the contact resistance increased to 4.8 mΩ, with an increase of less than 50%, meeting the reliability requirements for electrical contact materials.

[0084] In this embodiment, the thickness of the block copolymer self-assembled film is controlled to be within 15 nm, and a faster spin coating speed and a shorter annealing time are used to reduce the film thickness. The thinner film helps to reduce the potential obstruction of the organic layer itself to the electrical and thermal conductivity of the metal-substrate interface, enabling a tighter bond between the gold conductive layer and the liquid crystal polymer substrate.

[0085] It should be noted that the number-average molecular weight of the block copolymers in the above embodiments is selected within the range of 30,000 g / mol to 150,000 g / mol. When the molecular weight is too low, the thermodynamic incompatibility driving force of the two segments is insufficient to drive ordered microphase separation; when the molecular weight is too high, the solution viscosity increases, which is not conducive to precise control of film thickness during spin coating or dip coating. When the mass fraction of poly(4-vinylpyridine) segments or poly(2-vinylpyridine) segments is between 25% and 50%, the corresponding microphase separation morphology is a structure in which spherical or short columnar domain regions are dispersed in the continuous phase of matrix segments. This structure can form isolated but periodically distributed chemical anchors on the film surface. If the proportion of functional segments is too low, the anchor areal density is insufficient, and the metal regions grown by adjacent anchors are difficult to overlap; if the proportion of functional segments is too high, the morphology changes to a layered or bicontinuous structure, the spatial distribution pattern of chemical anchors changes, and the effect of inducing uniform nucleation of metal droplets decreases.

[0086] The choice of annealing temperature depends on the composition of the block copolymer. For the polystyrene-block-poly(4-vinylpyridine) series, the glass transition temperature of the polystyrene segment is approximately 100°C, and that of the poly(4-vinylpyridine) segment is approximately 140°C. The annealing temperature needs to be higher than the glass transition temperatures of both segments to ensure sufficient molecular chain mobility, while avoiding excessive temperatures that could lead to film degradation. An annealing temperature range of 120°C to 150°C balances phase separation kinetics and film thermal stability.

[0087] The laser energy density of LMC laser sputtering is a crucial parameter affecting the transfer quality of metal droplets and the protection of thin films. When the energy density is below 1×10⁻⁶, the laser energy density becomes significantly lower. 5 At a specific energy density (W / cm²), the metal film cannot fully melt and vaporize, resulting in low transfer efficiency and insufficient deposited metal to form a continuous conductive layer; when the energy density exceeds 5 × 10⁻⁶ W / cm², the metal film cannot fully melt and vaporize, leading to low transfer efficiency and insufficient deposited metal to form a continuous conductive layer. 5 At W / cm², laser ablation is too intense, with excessively high molten droplet temperature and velocity, potentially breaking down or ablating the block copolymer film and disrupting the chemical anchoring structure. At 1×10⁻⁶ W / cm², the laser ablation is too vigorous, with excessively high molten droplet temperature and velocity, which may break down or ablate the block copolymer film, destroying the chemical anchoring structure. 5 W / cm² up to 5×10 5 Within the energy density range of W / cm², combined with appropriate pulse width and donor-acceptor spacing, efficient metal transfer can be achieved while maintaining the integrity and functionality of self-assembled films.

[0088] Regarding film thickness, the thickness of self-assembled films ranges from 10 nm to 50 nm. When the film thickness is less than 10 nm, the effective distribution depth of chemical anchors in the vertical direction is insufficient to effectively capture molten droplets arriving from different angles; when the film thickness exceeds 50 nm, the hindering effect of the organic layer on current conduction becomes significant, and the interfacial contact resistance between the metal layer and the substrate increases. A suitable film thickness can provide sufficient chemical anchor capture capacity while minimizing the adverse effects on conductivity.

[0089] The thickness of the metal thin film donor substrate is selected in the range of 200nm to 500nm. Donor metal thin films below 200nm are easily completely consumed during laser ablation, and the amount of metal transferred in a single operation is small, requiring more repeated sputtering to achieve the target thickness. Donor metal thin films above 500nm require higher laser energy to achieve complete transfer, which increases the difficulty of process control and the thermally affected area.

[0090] The number of sputtering cycles is determined based on the target conductive layer thickness. The thickness of the metal layer formed by a single sputtering is approximately 30% to 50% of the donor metal film thickness. After the initial sputtering utilizes chemical anchoring to induce the formation of a continuous conductive underlayer, subsequent sputtered metal droplets deposit directly on and thicken the existing metal layer. This stage offers higher deposition efficiency and is unaffected by the substrate surface properties. The final conductive layer thickness ranges from 500 nm to 5 μm, with corresponding resistivity reduced to 3 μΩ·cm to 10 μΩ·cm, meeting diverse application requirements from general conductive circuits to high-conductivity electrical contact devices.

[0091] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A method for optimizing the conductivity of a metal surface layer on a plastic substrate by LMC laser sputtering, characterized in that, The method includes the following steps: Step 1: A block copolymer self-assembled film is formed on the surface of a plastic substrate. The block copolymer includes anchoring segments and functional segments. The anchoring segments are attached to the surface of the plastic substrate through intermolecular interactions. The functional segments carry chemical functional groups that can coordinate with metal atoms. After annealing, the block copolymer self-assembled film forms a nanoscale periodic microphase separation structure. The functional segments form periodically distributed chemical anchors on the surface of the self-assembled film. Step 2: Using LMC laser sputtering, a metal film is transferred from the donor substrate to the surface of the plastic substrate. The molten metal droplets generated by sputtering impact the surface of the self-assembled film. The metal atoms in the metal droplets coordinate and bond with the chemical anchor points, preferentially nucleating at the chemical anchor points and spreading radially to form a continuous conductive metal layer.

2. The method for optimizing the conductivity of a metal surface layer on a plastic substrate by LMC laser sputtering according to claim 1, characterized in that, In step one, the block copolymer is a polystyrene-block-poly(4-vinylpyridine), the anchoring segment is a polystyrene segment, the functional segment is a poly(4-vinylpyridine) segment, the chemical functional group is a pyridine nitrogen atom, the number average molecular weight of the block copolymer is 30,000 g / mol to 150,000 g / mol, and the mass fraction of the poly(4-vinylpyridine) segment is 25% to 50%.

3. The method for optimizing the conductivity of a metal surface layer on a plastic substrate by LMC laser sputtering according to claim 1, characterized in that, In step one, the block copolymer is selected from any one of the following groups: Polystyrene-intercalated poly(2-vinylpyridine); Polymethyl methacrylate-intercalated (4-vinylpyridine); Styrene-vinylpyridine-styrene triblock copolymer; Block copolymers with thiol functional groups grafted onto their surfaces; Surface grafted block copolymers containing amino functional groups.

4. The method for optimizing the conductivity of a metal surface layer on a plastic substrate by LMC laser sputtering according to claim 1, characterized in that, In step one, the method for preparing the block copolymer self-assembled film includes spin coating or dip coating. The spin coating method has a spin speed of 2000 rpm to 4000 rpm and a spin coating time of 30 seconds to 60 seconds. The dip coating method has a pull-up speed of 0.5 mm / s to 2 mm / s and a dip coating time of 30 seconds to 60 seconds. The thickness of the block copolymer self-assembled film is 10 nm to 50 nm.

5. The method for optimizing the conductivity of a metal surface layer on a plastic substrate by LMC laser sputtering according to claim 1, characterized in that, In step one, the annealing process is carried out in a vacuum oven at a temperature of 120°C to 150°C for 2 to 4 hours, and the size of the nanoscale periodic microphase separation structure is 5 nm to 20 nm.

6. The method for optimizing the conductivity of a metal surface layer on a plastic substrate by LMC laser sputtering according to claim 1, characterized in that, In step one, before forming the block copolymer self-assembled film, the plastic substrate is further subjected to surface pretreatment, which is oxygen plasma treatment or ultraviolet ozone treatment. The oxygen plasma treatment has a power of 50W to 100W and a treatment time of 30 seconds to 60 seconds.

7. The method for optimizing the conductivity of a metal surface layer on a plastic substrate by LMC laser sputtering according to claim 1, characterized in that, In step two, the LMC laser sputtering process uses a laser wavelength of 532nm or 1064nm, a laser pulse width of 10ns to 50ns, and a laser energy density of 1×10⁻⁶. 5 W / cm² up to 5×10 5 W / cm², the distance between the donor substrate and the plastic substrate is 50μm to 200μm.

8. The method for optimizing the conductivity of a metal surface layer on a plastic substrate by LMC laser sputtering according to claim 1, characterized in that, In step two, the thickness of the metal film is 200nm to 500nm, and the metal film is selected from pure copper film, pure silver film, copper-silver alloy film, copper-nickel alloy film, gold film or platinum film.

9. The method for optimizing the conductivity of a metal surface layer on a plastic substrate by LMC laser sputtering according to claim 1, characterized in that, Step two further includes performing at least one repeated LMC laser sputtering on the continuous conductive metal layer deposited on the surface of the plastic substrate, so that the continuous conductive metal layer accumulates and thickens, and the final thickness of the continuous conductive metal layer is 500 nm to 5 μm.

10. The method for optimizing the conductivity of a metal surface layer on a plastic substrate by LMC laser sputtering according to claim 1, characterized in that, The plastic substrate is selected from any one of the following groups: Polycarbonate; Acrylonitrile-butadiene-styrene copolymer; Polymethyl methacrylate; Polypropylene; Polyethylene; Polyethylene terephthalate; Polyetheretherketone; Liquid crystal polymer; Polystyrene.

Citation Information

Patent Citations

  • Manufacturing method of plastic part and its surface conductor structure

    CN103313521B

  • A laser-induced forward transfer method for forming highly conductive metal structures

    CN117637246B